2006
DOI: 10.1097/01.ta.0000229052.75460.c2
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammatory Response Syndrome and Nosocomial Infection in Trauma

Abstract: SIRS is predictive of nosocomial infection in trauma through postinjury day 21. Nosocomial infection should be considered as a treatable cause of SIRS in trauma patients, and early diagnostic interventions should be initiated to evaluate for potential causes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 38 publications
2
66
0
2
Order By: Relevance
“…A recent report has shown that patients with blunt injuries (84%) and penetrating injuries (16%) developed a nosocomial infection in 45.4% of the cases (15). To determine whether decreased numbers of CD4-or CD8-expressing cells play a role in a subsequent infection, we continued our studies with CD4-or CD8-deficient mice using a physiologically relevant model of sepsis.…”
Section: Cd4 and Cd8 T-cell Numbers Are Decreased After Blunt Traumamentioning
confidence: 99%
“…A recent report has shown that patients with blunt injuries (84%) and penetrating injuries (16%) developed a nosocomial infection in 45.4% of the cases (15). To determine whether decreased numbers of CD4-or CD8-expressing cells play a role in a subsequent infection, we continued our studies with CD4-or CD8-deficient mice using a physiologically relevant model of sepsis.…”
Section: Cd4 and Cd8 T-cell Numbers Are Decreased After Blunt Traumamentioning
confidence: 99%
“…It has been recently reported that ~45% of patients suffering blunt or penetrating trauma develop nosocomial infections [15]. To determine whether decreased numbers of γδ T cells mediate the immune response during a subsequent infection, we examined the response of γδ T cell-deficient mice in a physiologically relevant model of sepsis.…”
Section: γδ T Cell Numbers Are Decreased Following Blunt Traumamentioning
confidence: 99%
“…This cytokine activates a system for the subsequent production of acute phase proteins and increases C-reactive protein (CRP) 1 . The severities of the immune disorders are proportional to the extent of the surgical trauma [1][2][3] . In addition to the cytokines' actions on wound healing, the mobilization of macrophages is responsible for the production of growth factors, such as vascular endothelial growth factor (VEGF), which are essential for the development of surgical scars and granulation tissue 4,5 .…”
Section: ■ Introductionmentioning
confidence: 99%